Strategi Mobilisasi Politik pada Pemilu 2019 di Indonesia - Dewi, Nevy Rusmarina; Mufarikhin, Mufarikhin; Rohmaniah, Dinda Alfiatur (POLITEA, 2019)
Democracy in Indonesia has developed rapidly after the reformation, this is evidenced by the improvement in the implementation of the democratic party event. The 2019 election is an election held simultaneously between legislative elections and the presidential election. Each party and party coalition presidential election support hand in hand to try to win the hearts of the people. Community participation is very important for the determination of the votes of both the legislature and the president. Each stakeholder seeks to influence the community by using mobilization efforts. Many of the mobilization strategies in this election were carried out by many parties. This study examines the strategy of political mobilization used in gaining votes in 2019 elections in Indonesia. Qualitative research methods are used to obtain results from research. The results of the study indicate that the strategy of political mobilization in the 2019 Election uses four strategies, namely: political identity, communication media, money politics, and the use of public figures. This strategy is very effective in influencing the masses in Indonesia. This is evidenced by the polarization between the two supporting camps, and the use of communication media, especially social media in the dissemination of information.